(untitled) (Journal of Engineering, 2018)
CO2 Gas is considered one of the unfavorable gases and it causes great air pollution. It’s possible to decrease this pollution by injecting gas in the oil reservoirs to provide a good miscibility and to increase the oil recovery factor. MMP was estimated by Peng Robinson equation of state (PR-EOS). South Rumila-63 (SULIAY) is involved for which the miscible displacement by is achievable based on the standard criteria for success EOR processes. A PVT report was available for the reservoir under study. It contains deferential liberation (DL) and constant composition expansion (CCE) tests. PVTi software is one of the (Eclipse V.2010) software’s packages, it has been used to achieve the goal. Many trials have been done to match the data of DL test by tuning some of the PR-EOS parameters through the regression analysis process, but no acceptable match was obtained especially for saturation pressure. However; splitting the mole fraction of (C6+) to many pseudo components was carried out, and then a regression analysis process was made again to improve the matching by tuning some of the PR-EOS parameters. A good estimate of saturation pressure and a good match of PVT properties was noted. Ternary diagram has been constructed to represent the phase behavior of -Oil and to calculate MMP for the South Rumila-63 (SULIAY) oil well.